The Role of Women in Da'wah (Case Study of the Muslimatan NU Branch, Jaddung Pragaan Village) - Ratna Sari binti Sukardin; Ahmad Zukfikar Ali (Penerbit Hellow Pustaka, 2025)
This study discusses the role of women in preaching in the organization